A Comparative Study of LiNCA Cathode Recycled from Spent Lithium-Ion Batteries and Synthesized from Metal Precursor - Jumari, Arif; Apriliani, Enni; Yudha, Cornelius Satria; Purwanto, Agus; Syahrial, Anne Zulfia; Pita Rengga, Wara Dyah (Indonesian Journal of Chemistry, 2024)
Spent lithium NCA (LiNCA) battery was recycled using organic and inorganic acids and the performances were compared against the cathode synthesized from precursor. The metals in the spent cathode were leached using sulfuric or citric acid and coprecipitated into ternary metal oxalate (TMO) after reduction and lithium separation. Subsequently, the coprecipitated solution was used for cathode synthesis. Leaching efficiencies for nickel, cobalt and aluminum using citric acid were 85.6, 94.1, and 99%, respectively, while the efficiencies using sulfuric acid were 96, 98, and 100%, respectively. TMO produced from coprecipitation had the same physical characteristics. It was important to acknowledge that all cathodes also had similar physical characteristics. The electrochemical tests showed that commercial cathodes had the highest capacity of 150 mAh/g. This was followed by those from precursors, sulfuric acid leaching, and citric acid leaching, which recorded 142, 135, and 130 mAh/g, respectively. Based on the cycle test at 1C, the sample from citric acid leaching was 86% after 20 cycles compared to others at 82–83%. The results suggested that spent LiNCA could be regenerated into new cathodes using acid with performance comparable to those synthesized from precursor. This presented a viable alternative for LiNCA cathode synthesis.